PERANAN MIKORIZA TERHADAP PERTUMBUHAN, SERAPAN P DAN Cd TANAMAN SAWI (Brassica juncea L.) SERTA KADAR P DAN Cd ANDISOL YANG DIBERI PUPUK FOSFAT ALAM - Yuli Sagala; Asmarlaili sahar Hanafiah; Razali Razali (Universitas Sumatera Utara, 2013)
This study aimed to determine the role of Mycorrhizae on plant Cd uptake P and mustard(Brasicca juncea L.) as well as the availability of P and Cd in fed Andisol phosphate fertilizer. Theresearch was conducted in the Greenhouse, Soil Biology Laboratory, and the Laboratory ofResearch and Technology Faculty of Agriculture, University of North Sumatra, Medan, in July2012-March 2013. This study uses a randomized block design (RBD) Factorial. The first treatmentwas a factor with two levels of mycorrhizal inoculum M0 (0g) and M1 (20g), the second factor isthe treatment of phosphate fertilizer (SP-36) with 4 dose levels, P0 (0g), P1 (0.97g), P2 (1.94g ),and P3 (3.88g) with 3 Deuteronomy thus obtained 2x4x3 = 24 experimental units. The parametersmeasured were the canopy dry weight, root dry weight, P uptake, mustard plant (Brasicca juncea L.)Cd uptake, the degree of mycorrhizal infection, levels availbility of P and Cd levels Andisol. Theresults showed that administration of Mycorrhizae increase the dry weight of the canopy, the degreeof infection of the roots, P uptake and plant-available soil P levels. Phosphate fertilizersincreased the dry weight of the plant canopy and P uptake, and tend to increase levels of P and Cdsoil and plant P uptake but not statistically.Keywords: andisol, phosphate fertilizer, and mycorrhizae.